Juridical Implementation of Distribution Assets for the Inheritance to Adopted by Islamic Law Compilation - Noor Handayani; Akhmad Khisni (Jurnal Akta, 2019)
The purpose of this study was to: 1) analyze the position adopted child's inheritance rights in Islamic Law Compilation (KHI). 2) to analyze the implementation of the division of property as inheritance to an adopted child Compilation of Islamic Law (KHI). 3) Analyze the legal consequences of the implementation of the division of property as inheritance to an adopted child Compilation of Islamic Law (KHI).This study was prepared using the type of normative juridical research, the research focused on reviewing the application of the rules or norms of positive law. This study uses the approach of legislation (statute approach) And the approach of the case (case approach). The data collection was obtained by interview and literature. Analysis of data using qualitative descriptive.The research results are: 1) Position Adopted in the Compilation of Islamic Law that adopted children may not be recognized to be the basis and cause of inherited, because the basic principle in Islamic inheritance law is their blood relations / nasab / descent. So as the solution according to Islamic law compilation is by jalam Award "was borrowed" on condition should not be more than 1/3 (one third). 2) The division of property as inheritance to an adopted child Compilation of Islamic Law (KHI) must meet two requirements that are required to accept the will not the beneficiary, the person who died both the grandfather and the grandmother has not provided to the child that must be made a will, the amount with other roads, such as grants for example, and if he has less than the sum was borrowed, then it should enhanced the will. 3) The role of the Notary in deed was borrowed for a foster child is doing what desired heir and explain all that heir to all the heirs, it is intended to provide clarity and legal certainty for all heirs of things execution of wills which heir to all his heirs.Keywords: Inheritance, Adopted, Compilation of Islamic Law.